Elementary School Teachers’ Perceptions of Science Practicum During the Limited Face-to-Face Learning Period - Efrina, Noviana (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2017)
This research aims to describe elementary school teachers’ perceptions of science practicum during the limited face-to-face learning period at State Elementary School 182/I Protected Forest in understanding teachers’ perceptions of science practicum during the limited face-to-face learning period. This research was conducted at State Elementary School 182/I Protected Forest. Research data was obtained by conducting interviews with class teachers who implemented science practicum (as main data) carrying out documentation (as supporting data). After conducting interviews and documentation, the data was analyzed qualitatively using Miles and Huberman data analysis. The results of this research indicate that primary school teachers’ perceptions of science practicum during the face-to-face learning period are limited, first of all, absorption of stimuli or objects from outside the individual. Science practicum teachers gain knowledge or information from several sources such as teacher books, student books, practice books, the internet and YouTube. Second, for understanding science practicum, the teacher understands science practicum using existing sources, from these sources he can understand the meaning of science practicum, the science practicum tools and materials used, and the steps for science practicum. The third is assessment or evaluation of science practicum. From the teacher’s responses there was a positive assessment of the science practicum. The conclusion obtained from this research is that the teacher’s perception of science practicum during limited face-to-face learning can be seen from the teacher’s response, from absorption of stimuli or objects from outside the individual, understanding or understanding and assessment or evaluation.